Control of Post Harvest Fungal Deterioration of Pineapple (Ananas comosus (L) Merr.) Using Extracts of Plant Origin in Nigeria - C, Amadioha A.; J, Anidobu R. (African Journal of Clinical Medicine and Pharmacy Research, 2024)
Post-harvest fungal deterioration of pineapple is the most important challenge in pineapple production value chain causing losses in both nutrient and market values. This research was undertaken to identify the fungal pathogens causing rot of pineapple fruits in storage and their control using the water and ethanol leaf extracts of Moringa oleifera, Azadirachta indica (Neem), and Carica payaya (pawpaw). Pathogenicity test of fungal isolates from infected pineapple fruit indicated Rhizopus stolonifer, Aspergillus niger and Fusarium solani as major pathogenic organisms causing storage rot of pineapple fruits. A. niger had the highest frequency of occurrence and most virulent recording the highest disease incidence and severity followed by R. solonfer and F. solani. The effects of both aqueous and ethanol extracts of the plant materials on rot development and spread in pineapple fruits by the pathogens showed that pineapple fruits sprayed with the plant extracts before inoculation of the pathogens recorded less disease incidence than those fruits spray-inoculated with pathogen before application of plant extracts suggesting that the extracts are better used as protectant before infection and development of disease. The ethanol leaf extracts were more effective than water extracts in reducing the disease incidence and severity of the pathogenic organisms in pineapple indicating that the solvent of extraction affected the antimicrobial activities of the test plant materials with ethanol extracting more active compounds than water as extracting solvent. The extracts of A. indica were most potent in the reduction of rot development and spread in pineapple indicating that the extracts contained more anti-fungal properties that affected the growth of the pathogenic organisms in vivo followed by extracts of C. papaya and M. oleifera. Extracts of these plant materials could therefore be exploited as pesticides of plant origin in the control of postharvest microbial deterioration of pineapple fruits and increase food production.